2021
DOI: 10.1101/2021.07.05.21260012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early management of severe COVID-19 coagulopathy should be guided by TEG®, microclot and platelet mapping

Abstract: The coronavirus disease 2019 (COVID-19) (SARS-Cov-2) has caused a worldwide, sudden and substantial increase in hospitalizations for pneumonia with multiorgan problems. An important issue is also that there is still no unified standard for the diagnosis and treatment of COVID-19. Substantial vascular events are significant accompaniments to lung complications in COVID-19 patients. Various papers have now also shown the significance of thromboelastrography (TEG) as point-of-care technology to determine the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 125 publications
(211 reference statements)
0
7
0
Order By: Relevance
“…29 45 In conjunction with this, our research group has suggested that fibrin amyloid microclot (currently available only as a research laboratory tool) might be of great importance to determine clotting pathology in individuals with acute COVID-19 infection. 29 36 Microclots are defined as fibrinogen (and other plasma proteins) that clot into an anomalous “amyloid” from fibrin (“fibrinaloid”) with higher than normal resistance to fibrinolysis, and a size range from 1 to 200 µm when measured on the longest axis. 27 Our group has previously shown amyloid fibrin deposits in numerous inflammatory conditions.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…29 45 In conjunction with this, our research group has suggested that fibrin amyloid microclot (currently available only as a research laboratory tool) might be of great importance to determine clotting pathology in individuals with acute COVID-19 infection. 29 36 Microclots are defined as fibrinogen (and other plasma proteins) that clot into an anomalous “amyloid” from fibrin (“fibrinaloid”) with higher than normal resistance to fibrinolysis, and a size range from 1 to 200 µm when measured on the longest axis. 27 Our group has previously shown amyloid fibrin deposits in numerous inflammatory conditions.…”
Section: Tablementioning
confidence: 99%
“…It is well established that the earlier variants (before omicron) caused severe disease and resulted in coagulopathies in critically ill patients. 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 In contrast, the heavily mutated omicron variants have been shown to have milder symptoms than the earlier variants. The five most prevalent symptoms during omicron infection were reported to be runny nose, rhinitis headache, fatigue (either mild or severe), sneezing, and sore throat.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Around 20% of COVID-19 patients rapidly progress to a severe illness that includes extensive thrombotic complications. 77 Patients may experience both thrombotic and hemorrhagic symptoms, due to overactivation of platelets altering normal clotting, or to secondary inflammation resulting in decreased platelet count and low fibrinogen, usually as a result of consumption. 12…”
Section: Left Atrial Appendage Closurementioning
confidence: 99%